Acute Cor Pulmonale in Veno-Venous Extracorporeal Membrane Oxygenation: Three Case Reports. Issue 6 (November 2018) - Dong, Erik R.; Ng, David G.; Ramzy, Danny; Chung, Joshua S.; Friedman, Oren; Combes, Alain; Arabia, Francisco A.; Nurok, Michael
Abstract : A retrospective review of three patients with acute respiratory distress syndrome (ARDS) and normal baseline right ventricular function admitted to the Cardiac Surgery Intensive Care Unit whom developed acute cor pulmonale while on veno-venous extracorporeal membrane oxygenation. These patients were diagnosed with ARDS using Berlin Criteria definitions and cannulated with a dual lumen (Avalon) cannula. Despite variations in history, presentation, and course, findings of acute cor pulmonale were encountered 4 to 6 weeks after extracorporeal membrane oxygenation cannulation. The potential mechanisms include thromboembolic burden to the pulmonary vasculature, hypoxemia, acidosis, the pathologic progression of ARDS, and chronic nonphysiologic flow to the right heart.